2022
DOI: 10.1249/mss.0000000000003054
|View full text |Cite|
|
Sign up to set email alerts
|

Reducing Sedentary Time and Whole-Body Insulin Sensitivity in Metabolic Syndrome: A 6-Month Randomized Controlled Trial

Abstract: Purpose: This study aimed to investigate whether a reduction in daily sedentary behavior (SB) improves insulin sensitivity in adults with metabolic syndrome in 6 months, without adding intentional exercise training. Methods: Sixty-four sedentary inactive middle-age adults with overweight and metabolic syndrome (mean (SD) age, 58 (7) yr; mean (SD) body mass index, 31.6 (4.3) kg•m −2 ; 27 men) were randomized into intervention and control groups. The 6-month individualized behavioral intervention supported by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(51 citation statements)
references
References 49 publications
3
47
1
Order By: Relevance
“…The accelerometry results of this study have been reported and discussed earlier. 15 The INT group reduced SB by 40 min/day and increased MVPA by 20 min whereas in the CON group SB and MVPA remained unchanged (group × time p < 0.05). 15 Furthermore, daily step count increased in both groups but significantly more in the INT group (group × time p = 0.001).…”
Section: Intervention Effectsmentioning
confidence: 82%
See 4 more Smart Citations
“…The accelerometry results of this study have been reported and discussed earlier. 15 The INT group reduced SB by 40 min/day and increased MVPA by 20 min whereas in the CON group SB and MVPA remained unchanged (group × time p < 0.05). 15 Furthermore, daily step count increased in both groups but significantly more in the INT group (group × time p = 0.001).…”
Section: Intervention Effectsmentioning
confidence: 82%
“…As reported earlier, baseline SB and PA were measured for 4 weeks (screening phase), and thereafter during the whole 6-month intervention. 15 Triaxial accelerometers attached to the right hip were used (UKK AM30, UKK Terveyspalvelut Oy, Tampere, Finland during screening, and Movesense, Suunto, Vantaa, Finland during the intervention). The participants were advised to wear the accelerometer during waking hours and to remove it when going to sleep or when the device could be exposed to water.…”
Section: Sedentary Behavior and Physical Activitymentioning
confidence: 99%
See 3 more Smart Citations